2017
DOI: 10.1080/07357907.2017.1310221
|View full text |Cite
|
Sign up to set email alerts
|

A Phase-2 Trial of Single Agent Axitinib as Maintenance Therapy Following First-Line Treatment With Modified FOLFOX/Bevacizumab in Patients With Metastatic Colorectal Cancer

Abstract: This phase-2 trial evaluated the efficacy of axitinib as maintenance therapy for patients with metastatic colorectal cancer (mCRC) following first-line treatment with FOLFOX/bevacizumab. Patients with mCRC received mFOLFOX/bevacizumab followed by axitinib maintenance after four cycles. The primary endpoint was progression-free survival (PFS). Seventy patients were enrolled. Common treatment-related toxicities were fatigue, nausea, diarrhea, and peripheral neuropathy during FOLFOX/bevacizumab treatment; and fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Compound 4 was evaluated in phase II trials for efficacy and safety as a first-line maintenance therapy for mCRC. In both trials, 4 demonstrated to be an effective agent in the first-line maintenance therapy of mCRC, a promising candidate for the maintenance therapy of mCRC [55,56]. A combination of 4 and navitoclax (ABT263, an antagonist of the Bcl-2 family with selective binding to the apoptosis suppressors Bcl-2 and Bcl-XL) has shown synergistic effects on RAmutant colon cancer cells.…”
Section: Nintedanib (1) (Methyl 2-hydroxy-3-[n-[4-[methyl-[2-(4-methy...mentioning
confidence: 99%
“…Compound 4 was evaluated in phase II trials for efficacy and safety as a first-line maintenance therapy for mCRC. In both trials, 4 demonstrated to be an effective agent in the first-line maintenance therapy of mCRC, a promising candidate for the maintenance therapy of mCRC [55,56]. A combination of 4 and navitoclax (ABT263, an antagonist of the Bcl-2 family with selective binding to the apoptosis suppressors Bcl-2 and Bcl-XL) has shown synergistic effects on RAmutant colon cancer cells.…”
Section: Nintedanib (1) (Methyl 2-hydroxy-3-[n-[4-[methyl-[2-(4-methy...mentioning
confidence: 99%
“…The initial oral dose of axitinib was 5 mg twice daily, and after 2 weeks of administration, the dose was increased to 7 mg twice daily in those patients that were able to tolerate axitinib well. As the primary endpoint, the median PFS was 8.3 months and the results showed that the efficacy of axitinib was comparable to that of other first-line maintenance drugs 60…”
Section: Clinical Trials In Mcrcmentioning
confidence: 92%
“…Various TKIs other than regorafenib are under investigation for pretreated mCRC patients in order to improve the outcome in this setting, with some showing efficacy and an acceptable safety profile (Table 4) [74][75][76][77][78][79][80]. III, double-blind, placebo-controlled.…”
Section: Regorafenibmentioning
confidence: 99%